2016
DOI: 10.4081/jphia.2015.486
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5S-Continuous Quality Improvement-Total Quality Management approach on staff motivation, patients’ waiting time and patient satisfaction with services at hospitals in Uganda

Abstract: This study aimed at analyzing the effect of 5S practice on staff motivation, patients’ waiting time and patient satisfaction with health services at hospitals in Uganda. Double-difference estimates were measured for 13 Regional Referral Hospitals and eight General Hospitals implementing 5S practice separately. The study for Regional Referral Hospitals revealed 5S practice had the effect on staff motivation in terms of commitment to work in the current hospital and waiting time in the dispensary in 10 hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 4 publications
(5 reference statements)
1
12
0
Order By: Relevance
“…The present study also indicated that although after implementation of the 5S management method, the quality of provided services was still less than the patients' expectations, 5S implementation had decreased the quality gap from the patients' perspective in all studied fields. The results were similar to the Tak et al study, which indicated that the 5S implementation is effective in raising staff incentive, decreasing the waiting time and satisfying patients from health services [20]. A study by Sharifirad et al showed that there is still much room for improvement and reformation of the existing gap between patients' expectations and perceptions.…”
Section: Discussionsupporting
confidence: 79%
“…The present study also indicated that although after implementation of the 5S management method, the quality of provided services was still less than the patients' expectations, 5S implementation had decreased the quality gap from the patients' perspective in all studied fields. The results were similar to the Tak et al study, which indicated that the 5S implementation is effective in raising staff incentive, decreasing the waiting time and satisfying patients from health services [20]. A study by Sharifirad et al showed that there is still much room for improvement and reformation of the existing gap between patients' expectations and perceptions.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study also show that top management commitment, team work and participation, process management, customer focus and satisfaction, resource management, organizational and cultural behavior, continuous improvement, and training and education are the best TQM principles applied to hospitals (Talib et al, 2011). Kaizen and TQM implementations can be increase employee motivation and shorter waiting times, but significant differences are not identified in patient satisfaction (Take et al, 2015). Increasing employee motivation is a factor that causes operational performance to have a significant positive effect on customer loyalty.…”
Section: Introductionmentioning
confidence: 75%
“…TQM in the context of health care environments is defined as satisfaction of patients, doctors, nurses, and suppliers and other interested groups, which can be achieved by implementing Kaizen implementation has a goal, such as making organizations learn better through small incremental changes towards improvement known as Kaizen events, associating with work culture to get endless improvements in quality and productivity efficiency, eliminating hidden costs from 7 (seven)seven waste) in the production process such as overproduction, waste of time, transportation waste, inventory waste, excess processing waste, motion waste, and production defects, provide added value to production operations so as to improve the quality of products at the lowest cost , shorten delivery times to customers, and make changes in a relatively short time and low cost (Paul & New, 2003). Kaizen can improve operational efficiency, improve service quality and reduce operational costs (Bwemelo, 2016), stating that the 5S-Kaizen-TQM practice can increase employee commitment and motivation, reduce waiting time and increase patient satisfaction (Take et al, 2015).…”
Section: Literature Review Total Quality Management (Tqm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic scholar Liu Zhiqiang (2001) put forward the theory of human resources management [9]. That is, according to individual ability, personal contribution, personal career interests, personal development potential, the importance of personal positions and personal social background, the organization of all employees are roughly divided into A, B, C three categories.…”
Section: State Of the Artmentioning
confidence: 99%